TNFRSF12A and CD38 Contribute to a Vicious Circle for Chronic Obstructive Pulmonary Disease by Engaging Senescence Pathways - Dong, Yan; Cao, Hongbao; Cao, Rongyuan; Baranova, Ancha (Frontiers in Cell and Developmental Biology, 2020)
Pathogenesis of chronic obstructive pulmonary disease (COPD) is dependent on chronic inflammation and is hypothesized to represent organ-specific senescence phenotype. Identification of senescence associated gene drivers for the development of COPD is warranted. By employing automated pipeline, we have compiled lists of the genes implicated in COPD (N=918) and of the genes changing their activity along with cell senescence (N=262), with a significant (p-value<7.06e-60) overlap between these datasets (N=89). A mega-analysis and a partial mega-analysis were conducted for gene sets linked to senescence but not yet to COPD, in 9 independent mRNA expression datasets comprised of tissue samples of COPD cases (N=171) and controls (N=256). Mega-analysis of expression has identified CD38 and TNFRSF12A (p-value<2.12e-8) as genes not yet explored in a context of senescence-COPD connection. Functional pathways enrichment analysis allowed to generate a model which explains accelerated aging phenotypes previously observed in COPD patients. Presented results call for investigation of the role of TNFRSF12A/ CD38 balance in establishing vicious cycle of unresolvable tissue remodeling in COPD lungs.